Characterizing the Biomedical Data-Sharing Landscape. Issue 1 (March 2019) - Villanueva, Angela G.; Cook-Deegan, Robert; Koenig, Barbara A.; Deverka, Patricia A.; Versalovic, Erika; McGuire, Amy L.; Majumder, Mary A.
Advances in technologies and biomedical informatics have expanded capacity to generate and share biomedical data. With a lens on genomic data, we present a typology characterizing the data-sharing landscape in biomedical research to advance understanding of the key stakeholders and existing data-sharing practices. The typology highlights the diversity of data-sharing efforts and facilitators and reveals how novel data-sharing efforts are challenging existing norms regarding the role of individuals whom the data describe.